2016
DOI: 10.1126/scitranslmed.aaf1938
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial targeting of TSLP, IL-25, and IL-33 in type 2 cytokine–driven inflammation and fibrosis

Abstract: *Thymic stromal lymphopoietin (TSLP), interleukin-25 (IL-25), and IL-33 are important initiators of type 2-associated mucosal inflammation and immunity. However, their role in the maintenance of progressive type 2 inflammation and fibrosis is much less clear. Using chronic models of helminth infection and allergic lung inflammation, we show that collective disruption of TSLP, IL-25, and IL-33 signaling suppresses chronic and progressive type 2 cytokinedriven inflammation and fibrosis. In a schistosome lung gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
137
3
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(150 citation statements)
references
References 64 publications
(91 reference statements)
6
137
3
4
Order By: Relevance
“…While the Manni et al paper discussed by Poynter complements our studies, it did not describe a neutrophilic response in the context of IL-13 blockade, which may be due to the brief time frame of their model, differences in epithelial activation or damage, and induction of inflammatory alarmins. In agreement with Lynch et al we look forward to the potential of IL-33 targeting therapeutics, though recent work we published using the chronic HDM mouse model suggests that blocking individual alarmins might have limited efficacy when disease is well established (23). These points suggest that modeling the diversity of asthmatic endotypes might require comparison of numerous chronic mouse models with a wide range of inflammatory stimuli.…”
supporting
confidence: 84%
“…While the Manni et al paper discussed by Poynter complements our studies, it did not describe a neutrophilic response in the context of IL-13 blockade, which may be due to the brief time frame of their model, differences in epithelial activation or damage, and induction of inflammatory alarmins. In agreement with Lynch et al we look forward to the potential of IL-33 targeting therapeutics, though recent work we published using the chronic HDM mouse model suggests that blocking individual alarmins might have limited efficacy when disease is well established (23). These points suggest that modeling the diversity of asthmatic endotypes might require comparison of numerous chronic mouse models with a wide range of inflammatory stimuli.…”
supporting
confidence: 84%
“…The first study that evaluated the combinatorial targeting of all 3 cytokines in vivo identified a redundant role for the 3 ECs and showed that type 2-driven fibrosis and inflammation could only be suppressed by disruption of all 3 signals. 6 More recently, a different strategy of targeting both IL-33 and IL-13 proved superior to targeting either pathways alone in a mouse model of allergic inflammation. 33 In our study, we found that ECs alone are not able to induce any notable phenotypic changes or effector functions in human ILC2s; however, a combination of IL-33 and TSLP was efficient at inducing both IL-5 and IL-13 production and significant upregulation of IL-17BR and TSLPR, which further increased when all 3 cytokines were combined, even in the absence of any other confounding aspects such as the addition of other cytokines, like IL-2 or IL-7, or the presence of other cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Having established a robust methodology for ILC isolation, we focused on how ECs could directly impact ILC2 behavior in vitro, and we assessed whether the redundancy that has been previously described for these cytokines 6 could also applied to ILC2 activation. ILC2s were stimulated with EC alone or in combination.…”
Section: Tslp Provides a Survival Advantage To Ilc2smentioning
confidence: 99%
“…These data provide further evidence for a link between IL-33 release and the secretion of type 2 inflammatory cytokines, such as IL-4, IL-5, IL-9 and IL-13. 8 The relationship between inflammation and IL-33 was further underpinned by the finding that intraperitoneal injections of recombinant IL-33 increased hepatic inflammation in both naive and BDL-injured livers when given 3 days prior to the BDL surgery. However, IL-33 alone failed to enhance the inflammatory response in sham-operated mice, suggesting that IL-33 has the capacity to increase the production of inflammatory cytokines only in injured livers.…”
mentioning
confidence: 99%